2002
DOI: 10.1053/jlts.2002.34640
|View full text |Cite
|
Sign up to set email alerts
|

Slowly tapering off steroids protects the graft against hepatitis C recurrence after liver transplantation

Abstract: Chronic hepatitis C represents a major clinical problem after liver transplantation, but factors influencing the recurrent disease have not been well characterized. We analyzed the clinical records of all the patients transplanted for hepatitis C virus (HW-related liver disease in our Center between 1991 and 1997. Eighty consecutive HCV-positive (+) patients (60 men, ages 28 to 64) survived more than 1 month after transplantation and were followed for a median of 45 months. Diagnosis of recurrent chronic hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
2
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 10 publications
4
80
2
2
Order By: Relevance
“…20 For hepatitis C, role of low dose steroids with slow taper is advocated by some studies [85][86][87] Most centers would continue prolonged low dose steroids in patients transplanted for autoimmune liver diseases. 20 …”
Section: Disease Specific Approachmentioning
confidence: 99%
“…20 For hepatitis C, role of low dose steroids with slow taper is advocated by some studies [85][86][87] Most centers would continue prolonged low dose steroids in patients transplanted for autoimmune liver diseases. 20 …”
Section: Disease Specific Approachmentioning
confidence: 99%
“…However, there also is evidence that withdrawal of corticosteroids may be harmful to HCV-infected patients undergoing liver transplantation. 12 Similarly, data for mycophenolate mofetil (MMF) are confusing. One study from Berlin showed that if MMF is added to the posttransplantation regimen, there is no change in HCV RNA levels or severity of disease (Fig.…”
Section: Maintenance Immunosuppression and Hcvmentioning
confidence: 99%
“…Thus, patients who had their CS dose tapered slower had less tissue damage. 34 In this study, five of six patients with decompensated cirrhosis were in the group with more rapid tapering of steroid therapy.…”
Section: Relationship Between Immunosuppressive Therapies and Chronicmentioning
confidence: 99%